Subregional Density of Neurons, Neurofibrillary Tangles and Amyloid Plaques in the Hippocampus of Patients With Alzheimer’s Disease - Furcila, Diana; Domínguez-Álvaro, Marta; DeFelipe, Javier; Alonso-Nanclares, Lidia (Frontiers in Neuroanatomy, 2019)
A variety of anatomical alterations have been reported in the hippocampal formation of patients with Alzheimer’s disease (AD) and these alterations have been correlated with cognitive symptoms in early stages of the disease, including impairment of declarative memory, loss of context and disorientation. The two major lesions are extracellular amyloid plaques, primarily consisting of amyloid-β (Aβ) peptide, and intracellular neurofibrillary tangles, which consist of filamentous aggregates of hyperphosphorylated tau protein (PHFTau). Nevertheless, how the density of plaques and neurofibrillary tangles relate to the severity of cell loss and cognitive decline is not yet clear. In the present study, we have analyzed the density of PHFTau-ir neurons and Aβ-ir plaques, and the possible neuronal loss, in DG, CA3, CA1 and subiculum from 11 demented AD patients. Using stereological quantitative methods (optical disectors), we found CA1 was the region most affected by the presence of both PHFTau-ir elements and Aβ-ir plaques, followed by the subiculum. By contrast, DG and CA3 were less affected by these pathological proteins. Therefore, the present study further emphasizes a correlation between the presence of numerous PHFTau-ir elements and Aβ-ir plaques and neuronal loss in CA1 but not in other hippocampal fields from demented AD patients.